Key performance indicators and predictors in Varsity Cup rugby - Sewry, Nicola (MRC/UCT RU for Exercise and Sport Medicine, 2015)
Rugby union is a popular sport worldwide, and due to the professional nature of the sport the demands on players continues to increase, resulting in acute and chronic fatigue. The aims of the study were to investigate the tools used to monitor and predict changes in training status and determine the effectiveness of these to: (i) measure the subjective nature of coaches and their selection relating to the players’ performance, and (ii) to use performance indicators to correlate to team performance. The University of Cape Town Rugby Varsity Cup Team (First XV squad) were monitored from their pre-pre-season until the end of their competitive season. Players completed a testing battery (anthropometry, strength, muscular endurance, speed and aerobic fitness) during the season, along with Rating of Perceived Exertion and body mass was recorded every practice. Players also completed the HIMs test (measure of heart rate recovery) weekly. Coaches rated players every practice on three variables and the matches were recorded and video analysis performed to determine key performance variables. Most of the players improved in their testing battery between pre-pre-season and pre-season. Average session load varied across the phases of the season and was highest in the pre-preseason. Change in load however, was not reflected by changes in heart rate recovery which remained relatively stable across the season. The players’ body mass varied throughout the tournament, with certain players having a larger coefficient of variation compared to others. There was no relationship between performance in the testing battery and selection for matches. The coaches all had different ratings for the players, with no correlation between players selected and those not selected. There was a correlation between the subjective rating of players in the week leading up to the match and the match ratings of Coach 3 (head coach). The Varsity Cup rugby union players followed similar trends described in previous literature in physiological testing batteries, training loads and player management. The novel aspect of this study was the collection of data from the coaches involved. This qualitative data provides insight into the coaches’ selection process or lack thereof within a team environment. The data also illustrates the differences between the coaches’ interpretation of the players’ “performance”. The Varsity Cup is a relatively young tournament and should be further investigated to properly understand the differences between it and professional and amateur rugby union.